EFFECTIVENESS OF BATCH AND INTERMITTENT EXPOSURE OF CONSTRUCTED WETLAND SUB SURFACE SYSTEM IN PB METAL DEGRADATION IN LABORATORY LIQUID WASTE USING COSTUS SPICATUS PLANT - Putu Primantari Vikana Suari (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
There are several types of built-up wetland systems, including subsurface runoff wetlands, surface runoff wetlands, and hybrid runoff wetlands. Among the three types, in this study, subsurface flow constructed wetlands were selected because they have the advantage of having smaller land requirements compared to other types of artificial land. In addition, this type of wetland is not mosquito-friendly because there is no standing water on its surface. This study used a batch and intermittent exposure system. The purpose of using this exposure system is to find out a good exposure system in removing Pb metal. Based on the results of the research and discussion, it can be concluded that the effectiveness of the batch exposure system is higher than the intermittent system, this is determined by the effectiveness of the highest Pb absorption in the batch system of 98.39% and the highest intermittent system of 91.06%.